UNCTAD Handbook of Statistics 2022 - United Nations Conference on Trade; Development (United Nations, 2022)
The UNCTAD Handbook of Statistics was first launched in 1967. Over the past 50 years, the handbook has evolved to incorporate new statistics and ensure that readers have access to the best possible information available. The 2021 edition of the Handbook continues in this tradition of excellence and innovation. As in previous years, this edition showcases 'nowcasted' estimates for total merchandised trade, total services trade and GDP. This publication provides a wide range of statistics and indicators relevant to the analysis of international trade, investment, and development.